2010
DOI: 10.1002/mnfr.200900323
|View full text |Cite
|
Sign up to set email alerts
|

Allyl isothiocyanate as a cancer chemopreventive phytochemical

Abstract: Allyl isothiocyanate (AITC), which occurs in many common cruciferous vegetables, is widely and often frequently consumed by humans. Besides antimicrobial activity against a wide spectrum of pathogens, it showed anticancer activity in both cultured cancer cells and animal models, although the underlining mechanisms remain largely undefined. Bioavailability of AITC is extremely high, as nearly 90% of orally administered AITC is absorbed. AITC absorbed in vivo is metabolized mainly through the mercapturic acid pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
168
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 206 publications
(173 citation statements)
references
References 73 publications
5
168
0
Order By: Relevance
“…Allyl isothiocyanate, the main breakdown product of sinigrin, has been shown to have several biological activities. Antimicrobial [Shin et al, 2004] and anticancer activity related to multimode mechanism of action [Xiao et al, 2003;Zhang et al, 2010], including the stimulation of cytoprotective protein and anti-infl ammatory activity, have been reported in the previous studies [Wagner et al, 2012]. The biological activity of horseradish has been discovered many centuries ago, and it was very often utilized for treatment purposes in the traditional medicine [Agneta et al, 2013].…”
Section: Introductionmentioning
confidence: 99%
“…Allyl isothiocyanate, the main breakdown product of sinigrin, has been shown to have several biological activities. Antimicrobial [Shin et al, 2004] and anticancer activity related to multimode mechanism of action [Xiao et al, 2003;Zhang et al, 2010], including the stimulation of cytoprotective protein and anti-infl ammatory activity, have been reported in the previous studies [Wagner et al, 2012]. The biological activity of horseradish has been discovered many centuries ago, and it was very often utilized for treatment purposes in the traditional medicine [Agneta et al, 2013].…”
Section: Introductionmentioning
confidence: 99%
“…AITC, also known as mustard oil and existing in dietary cruciferous vegetables, is one of the common naturally occurring isothiocyanates (ITCs) (34,35). It is demonstrated that AITC promoted cell cycle arrest (36,37) and induced apoptosis (34,38) in many types of cancer cells. Therefore, AITC may have potential as dietary chemoprevention/treatment agent (34).…”
Section: Discussionmentioning
confidence: 99%
“…AITC shows bactericidal and fungicidal activities as well as anticancer activity with inhibition of cell proliferation, cell cycle arrest and apoptosis induction and tumor growth inhibition (5,8).…”
Section: Fig2 Conversion Of Sinigrin To Allyl Isothiocyanatementioning
confidence: 99%